Apakah Kecerdasan Intelektual, Kecerdasan Emosional Dan Kecerdasan Spiritual Berpengaruh Terhadap Motivasi Kerja Karyawan ? - palinggi, yonathan; Pardomuan Sirait, Sihol; Raharjo , Sugeng (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract: The purpose of this study was to determine and examine the influence of intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ) on employee motivation at PT. Telesindo Shop Tenggarong Branch. The sampling technique was carried out by means of a census which amounted to 39 with multiple regression analysis tools. The results showed that, first, the variables of intellectual intelligence, emotional intelligence, and spiritual intelligence together (simultaneously) were able to show their influence on the work motivation of employees of PT. Telesindo Shop Tenggarong Branch. The R number is 0.824, which means that the correlation between intellectual intelligence, emotional intelligence, and spiritual intelligence with employee work motivation has a very strong relationship. Second, from the three partial correlation test results, it can be seen that the value of the spiritual intelligence variable is the largest compared to other variables at 0.713 then followed by the intellectual intelligence and emotional intelligence variables so that the spiritual intelligence variable is the most dominant variable affecting the work motivation of PT. Telesindo Shop Tenggarong Branch, so the hypothesis is rejected. Keywords: intellectual intelligence, emotional intelligence, spiritual intelligence, work motivation